MORPHOLOGY OF OCCLUSAL SURFACE OF DECIDUOUS MOLARS AFTER ENAMEL ACID ETCHING - N.V. Bidenko (Український стоматологічний альманах, 2018)
Composites and compomers are the dental materials for restoration of permanent and primary teeth and for caries prevention – fissure sealing. They are used with adhesive systems which provides for micromechanical retention and need acid etching of dental tissues before application. However differences between morphology of permanent and deciduous dental tissues determine some morphological peculiarities of result of deciduous enamel etching. There are only few researches devoted to occlusal enamel morphology after acid etching.